A Problem-Solving Court for Crimes Against Older Adults - George B. Pesta; Julie N. Brancale; Thomas G. Blomberg (Laws)
The growth of the older adult population, their wealth accumulation, and vulnerabilities from aging have contributed to increasing rates of abuse, fraud, and financial exploitation. However, the current responses and services are fragmented and ineffectual. This paper develops a novel strategy for addressing the variation in response and victim service provision through the development of a problem-solving court that is informed by the principles of restorative justice. Given the unique challenges, cases, and population, a problem-solving court for crimes against older adults will provide tailored interventions, responses, and sanctions while ensuring that older adult victims and their communities are at the center of the criminal justice process and that their needs are prioritized. Research on problem-solving courts; restorative justice; and older adult abuse, fraud, and financial exploitation are integrated with data from a case study of older adult financial exploitation in a large retirement community to develop the model problem-solving court. Consistent with best practices in victim services, the model court will provide comprehensive services in a one-stop location, while simultaneously increasing accountability for offenders who prey on this vulnerable population. The paper concludes with a plan to guide the implementation and evaluation of the proposed model problem-solving court for older adult abuse, fraud, and exploitation.